KABUKI SYNDROME AND EPILEPSY - Marina Zhitomirskaya; Galina Treskina; Nina Dengina; Galina Odinstova (MNJ (Malang Neurology Journal), 2022)
Background: Kabuki syndrome is a rare disease. In 2018, a global consensus on diagnostic criteria for Kabuki syndrome (KS) was published, diagnosing KS both with and without molecular genetic confirmation. Neurological symptoms are a major clinical problem in more than 80% of cases. Seizures occur with a frequency of 10% to 40% in Kabuki syndrome. Various degrees of severity of epilepsy in KS have been reported. There are isolated cases of West syndrome in KS worldwide. Objective: To investigate the frequency of epilepsy in KS and the features of West syndrome comorbid with KS, using evidence from reviews and describing the clinical presentation based on the history of a patient with molecularly positive KS. Methods: The study design was a two-centre retrospective observational study. Study subjects were paediatric patients with genetically verified KS. We conducted our own observation of 4 patients with KS and detailed a clinical case of a male patient with West syndrome in KS. Results: Epilepsy was found in 2 patients. Onset of epilepsy at 1.5 and 20 months of age. Both cases were characterised by a severe course of epilepsy. A rare form of epilepsy in KS, West syndrome, was described in patient M. Initial complaints included first seizures and delay  in psychomotor development from 1.5 months of age. The clinical features of West syndrome, an electroencephalographic image, MRI of the brain, and the patient's seizure management were presented. Conclusion: Epilepsy in KS is not an uncommon clinical symptom that exacerbates the underlying disease. KS in combination with West syndrome exacerbates neurological deficits and leads to a significant delay in psycholinguistic and psychomotor development against a background of low efficacy of medication and differential effects of hormones and ketogenic diet.